Problems of organizing and conducting extra-course work in geography - Pohrebskyi, Taras H. (Волинський національний університет імені Лесі Українки, 2025)
At the current stage of development of general secondary education, extracurricular work in general and geography in particular is experiencing a difficult situation, remaining a weak link in the overall educational process. The lack of systematicity and purposefulness, the episodic nature of educational extracurricular activities, in which only individual children participate, the decrease in the number of interest groups – all this leads to the fact that children's school life ends with the bell from the last lesson. Modern leisure infrastructure offers children such a rich selection of interesting and vibrant options for organizing their free time that schools simply cannot compete with them. Computer clubs, children's entertainment rooms, centers and complexes, parks for entertainment and recreation, play spaces and playgrounds, interactive zones, laser tag, quests, etc. – all this attracts children much more than extracurricular activities at school. Children are becoming more and more addicted to entertainment, computer games, and gadgets, and are less and less willing to study, especially outside of the classroom
Keywords: geography; extra-course work; conducting extra-course work; рroblems extra-course work; 37.016:91:0046